2013
DOI: 10.3233/jad-121891
|View full text |Cite
|
Sign up to set email alerts
|

Oatp1a4 and an L-Thyroxine-Sensitive Transporter Mediate the Mouse Blood-Brain Barrier Transport of Amyloid-β Peptide

Abstract: The influx of amyloid-β peptide (Aβ) across the blood-brain barrier is partly mediated by the receptor for advanced glycation end products (RAGE). But other transporters, like Oatp (organic anion transporter polypeptide, SLC21) transporters, could also be involved. We used in situ brain perfusion to show that rosuvastatin and taurocholate, two established Oatp1a4 substrates, decreased (5-fold) the Clup of [3H]Aβ while L-thyroxine increased it (5.5-fold). We demonstrated an interaction between Aβ and Oatp1a4 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Multiple studies have made clear that amyloid β peptide (Aβ) can move from brain to the peripheral circulation [e.g., 13] and from the peripheral circulation to brain [e.g., 4,5]. As such, the disposition of circulating Aβ may be pathophysiologically important.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have made clear that amyloid β peptide (Aβ) can move from brain to the peripheral circulation [e.g., 13] and from the peripheral circulation to brain [e.g., 4,5]. As such, the disposition of circulating Aβ may be pathophysiologically important.…”
Section: Introductionmentioning
confidence: 99%
“…19 Although in mice it has been suggested that the organic anion transporter polypeptide (Oatp1a4) is responsible for importing Aβ into the CNS, no comparable transporter has been identified in humans. 20 Therefore this loss of BBB integrity may simply lead to an increase in the influx of Aβ into the brain. Moreover, RAGE-dependent signaling mediates downregulation of exporters of Aβ, 21 upregulation of β-secretase, 22 neuroinflammatory responses, 23 and stimulates tau phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of TA, the uptake of 125 I-T 4 into some brain tissues, such as ER and CAP, was increased. This suggests an interaction between TA and OATP 1a4 since TA was proven to be an OATP 1a4 substrate and sensitive transporter (Do et al, 2013 ). This agrees with a previous study which demonstrated that OATP2 and OATP3 mediate TH transport when their mRNA is injected into xenopus oocytes (Abe et al, 2002 ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has concentrated on studying the transport direction of T 4 from blood into the brain across the BBB suggesting a role for organic anion transporting polypeptides (OATP) such as OATP 1a4, 1c1, 2, 3, and 14, which are mainly localized at the blood side of the BBB (Abe et al, 1998 ; Gao and Meier, 2001 ; Mayerl et al, 2012 ; Do et al, 2013 ) and CP (Gao et al, 1999 ; Gao and Meier, 2001 ; Mayerl et al, 2012 ). On the other hand, others have demonstrated a role for OATP2 and multiple drug resistance 1 (MDR1) in the transport of 125 I-T 4 at the basolateral side of the isolated perfused sheep CPs (Preston and Segal, 1992 ).…”
Section: Introductionmentioning
confidence: 99%